Electronic and structural properties of ultra-thin metalic films on metal surfaces : dissertation - Valla, Tonica (T. Valla, 1996)
Abstract: This work presents experimental results of investigations of structural and electronic properties of copper, silver and gold ultra-thin films on a clean and well-ordered vanadium (100) surface. A detailed procedure required to obtain atomically clean and well-ordered vanadium (100) surface is described. The work function of the clean and well ordered V(100) is found by both, the UP spectrum width and the PAX measurements to be 4.1+-0.1eV. The electronic structure of the V(100) surface has been studied by means of angularly resolved photoelectron spectroscopy (ARUPS) and momentum (k)- resolved inverse photoemission spectroscopy (KRIPES). We have determined electron energy band dispersion of the vanadium valence bands along the H-G-N high symmetry direction of the bulk Brillouin zone by using HeI radiation (21.2 eV).